E-Teach Performance: A Scale to Evaluate Teaching Performance in Virtual Environments in Higher Education Programs for Adults - García-Salirrosas, Elizabeth-Emperatriz (2022)
The study proposes an instrument to evaluate teaching performance in virtual environments (E-Teach Performance), identifying 17 items, which makes it an easy-to-apply instrument for evaluating teacher performance that provides online teaching. The pilot test consisted of 222 participants who belong to a sector of working adult students who stated that they were enrolled during the first semester of 2021. The items were formulated after having carried out an exhaustive review of the literature to later be evaluated by experts who guaranteed the content of the construct. Exploratory and confirmatory factor analysis were applied to evaluate the proposed model, the results allowed to know a scale of two dimensions which were called: (1) Virtual Teaching Collaboration and (2) Virtual Teaching Accompaniment. The statistical analyzes showed a good fit of the model; in this way, this scale allows the authors to provide the scientific and university community with a reliable instrument to be applied both in future research and to evaluate university teachers who work in virtual environments.